A comparison of the gut contents of Ambassis vachellii (Richard, 1846) and Ambassis kopsii (Bleeker, 1858) in Conception, Iloilo. - Wong, Hazel Jynn (2017.)
Studying the different feeding habits and diet composition of the fishes provides a better understanding of how organisms are interrelated in the food web as reflected in their feeding patterns (Zacharia, 2014). Ambassis make up a genus of closely related species that occur widely in both tropical and sub-tropical coastal waters and estuaries of the Indo-Pacific (Martin & Blaber, 1983). This study aims to analyze and compare the diet composition of two co-occuring Ambassis species; Ambassis vachellii and Ambassis kopsii which were collected from Plandico Bay, Conception, Iloilo. Specimens used for this study were collected from pushnet catches sampled from August 2011 to December 2011. The standard length, body weight and gut weight of each individual were recorded. Gut contents were examined under a dissecting microscope and prey items were identified. The frequency of occurrence (FOC) of the identified prey item was calculated and the COMM program was used to compare the food items. T-test was used to compare the amount of chime between the two species. A total of 121 guts were examined with 5 empty guts and 116 contained different prey items. The mean amount of chime in A. kopskii which was 53%, is significantly lower than that of A. vachellii with 81%. Out of the nineteen prey items found in the gut of A. vachellii, the most abundant non-chyme food item was the calanoids, while from the thirty-one prey items found in the gut of A. kopskii, the most abundant prey item was the sergestid shrimp (Lucifer). The amount of chime in Ambassis vachellii is much higher compared to that of Ambassis kopskii, this may be due to the differences in intestine morphology and tme of active feeding. The study revealed that their feeding habits are more related to their sizes and not to their being different species.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Ambassis Vachellii -- Feeding habits; Ambassis Kopsii -- Feeding habits; Frequency of occurence; Chyme; Ambassis Vachellii; Ambassis Kopsii